2018
DOI: 10.1124/dmd.118.084657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 19-(S/R)Hydroxyeicosatetraenoic Acid as the First Endogenous Noncompetitive Inhibitor of Cytochrome P450 1B1 with Enantioselective Activity

Abstract: The overexpression of cytochrome P450 1B1 (CYP1B1) is a common characteristic of several diseases and conditions, such as inflammation, cancer, and cardiac hypertrophy. CYP1B1 is believed to contribute to pathogenesis of these diseases by mediating the formation of toxic compounds, either from exogenous or endogenous origin. We recently reported that an arachidonic acid metabolite, 19(S/R-)hydroxyeicosatetraenoic (HETE) acid, protects from cardiac hypertrophy by inhibiting the formation of toxic compounds, mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is protected against angiotensin II-induced cellular hypertrophy by reducing the level of pro-inflammatory midchain HETEs. Also, it noncompetitively inhibited the catalytic activity of CYP1B1, decreased the levels of lipoxygenase and cyclooxygenase-2 enzymes, and decreased the levels of IL-6 and IL-8 [18,101]. Strategies to enhance the levels of subterminal HETEs in the body include using specific CYP modulators such as isoniazid, a well-established inducer of hepatic CYP2E1, that increase the production of endogenous 19-HETE levels as well as using subterminal HETE synthetic analogs [29,30,102].…”
Section: Could the Modulation Of Subterminal Hydroxyeicosatetraenoic mentioning
confidence: 99%
“…It is protected against angiotensin II-induced cellular hypertrophy by reducing the level of pro-inflammatory midchain HETEs. Also, it noncompetitively inhibited the catalytic activity of CYP1B1, decreased the levels of lipoxygenase and cyclooxygenase-2 enzymes, and decreased the levels of IL-6 and IL-8 [18,101]. Strategies to enhance the levels of subterminal HETEs in the body include using specific CYP modulators such as isoniazid, a well-established inducer of hepatic CYP2E1, that increase the production of endogenous 19-HETE levels as well as using subterminal HETE synthetic analogs [29,30,102].…”
Section: Could the Modulation Of Subterminal Hydroxyeicosatetraenoic mentioning
confidence: 99%
“…A major interest of the El-Kadi group is the role of P450s in arachidonic acid metabolism (El-Sherbeni and El-Kadi, 2014) and alterations in these pathways in various disease models including: doxorubicin nephrotoxicity, hepatotoxicity (Zordoky et al, 2011), and cardiotoxicity (Alsaad et al, 2012); isoproterenol-induced cardiac hypertrophy (Zordoky et al, 2008;Althurwi et al, 2015); and angiotensin II-induced cardiac hypertrophy (Shoieb and El-Kadi, 2018;Alammari et al, 2023). Interestingly, this group also showed that 19(S)-hydroxyeicosatetraenoic acid is a more potent endogenous noncompetitive inhibitor of human CYP1B1 than the R-enantiomer (Shoieb et al, 2019).…”
Section: Prairie Provinces (Alberta Saskatchewan Manitoba)mentioning
confidence: 99%
“…Over the last few decades, several studies have shown that the Ep-PUFAs likely act stereospecifically [ 100 , 109 , 110 , 111 ]. In addition to Ep-PUFAs, the biological functions of hydroxy-PUFAs are also stereo- and regioselective [ 22 , 112 , 113 , 114 , 115 ].…”
Section: Cyp: a Key Monooxygenase Enzyme In Pufas Metabolismmentioning
confidence: 99%